The young Victoria [videorecording (DVD)] - Vallée, Jean-Marc; Blunt, Emily; Friend, Rupert; Bettany, Paul, 1971-; Richardson, Miranda; Broadbent, Jim; Kretschmann, Thomas, 1962-; Strong, Mark, 1963-; Walter, Harriet; Glover, Julian, 1935- (Sony Pictures Home Entertainment, 2010)
Chronicles the life and times of Queen Victoria from her childhood to her early rise to power and the first turbulent years of her rule. Her romantic relationship and eventual marriage to Prince Albert culminates in a royal power struggle which ultimately is the key to her happiness when she comes to the realization that he is someone she can fully trust and believe in.